Atmospheric deposition of microplastics in urban, rural, forest environments: A case study of Thulamela Local Municipality - Thendo Mutshekwa; Fulufhelo Mulaudzi; Vuledzani P. Maiyana; Lubabalo Mofu; Linton F. Munyai; Florence M. Murungweni (PLoS ONE, 2025)
Microplastic (MP) pollution, a pressing environmental issue globally, has received considerable attention in marine, freshwater and terrestrial environments. However, studies on the deposition of airborne MPs, particularly in Southern African regions, have received less attention. As such, the current study aimed at investigating the atmospheric deposition of MPs across three different environments, namely urban, rural and forest in the Thulamela Local Municipality, Limpopo, South Africa. We hypothesised that MP deposition will exhibit significant differences between different environments, with the urban environment having the highest MP deposition fluxes due to the dense population in the area and high human activities. The study results showed that MP deposition fluxes varied significantly across the environments, ranging from 90.51 ± 15.19 – 355.64 ± 47.65 particles/m2/day, with an overall average of 211.87 ± 31.44 particles/m2/day. The highest deposition was recorded in urban environment, while the lowest was observed in the forested environment. The overall deposited MPs were mainly transparent fibres and polyethylene terephthalate (PET). Furthermore, MP deposition found in the forest environment demonstrated a strong positive correlation with rainfall, suggesting that rainfall events play a significant role in the transporting and deposition of MP. The study further shed light on the possible fate of urban and rural atmospheric deposition, which has implications for pristine environments, indicating the transport and potential ecological impacts of MP pollution even in less populated and isolated environments.